2015
DOI: 10.4236/jssm.2015.86086
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Documentation through Monthly Audits in Butare Teaching Hospital, Rwanda

Abstract: Creditable and timely clinical documentation is an essential component in patient care quality improvement. We designed and implemented a practical clinical audit process as a way of measuring and improving quality of clinical care in Rwanda; as well as to enhance the compliance score according to the hospital accreditation standards. The project took place at Central University Hospital in Butare (CHUB). A pre-and post-intervention study was used to examine the impact of creating a standardized auditing syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…To date, much of the literature on improving health management has been conducted at the level of health centers or hospitals and has largely demonstrated that practical education and mentoring in management can promote significant improvements in the quality and consistency of health service delivery [212]. These studies have tracked a variety of health service measures such as waiting times [2, 5], pharmacy stock outs [4, 6], human resource management [6, 7], infection control processes [6], medical record availability [4, 9], and information system implementation and data monitoring [1012].…”
Section: Introductionmentioning
confidence: 99%
“…To date, much of the literature on improving health management has been conducted at the level of health centers or hospitals and has largely demonstrated that practical education and mentoring in management can promote significant improvements in the quality and consistency of health service delivery [212]. These studies have tracked a variety of health service measures such as waiting times [2, 5], pharmacy stock outs [4, 6], human resource management [6, 7], infection control processes [6], medical record availability [4, 9], and information system implementation and data monitoring [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Despite wide recognition of the importance of good nursing documentation practices, the quality of such documentation in LMICs remains poor. There are many facets to the problem including missing, insufficient, and unclear information in clinical records; poor completion of forms; incorrectly recorded patient identifiers with missing signatures, dates, and times; and insufficient use of discharge summaries and provision of care plans [7,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous efforts aiming to improve the quality of nursing documentation have been undertaken. Evidence-based approaches to improving documentation include interventions such as national clinical audits with data feedback [21,22], the availability of documentation policies and guidelines [10], information sharing [23], provision of training [24][25][26], strengthening nursing hospital leadership, engaging key staff into improvement processes [9], and the use of a framework for recording nursing daily free-text notes [26,27]. Nursing documentation can also be improved by indirect workforce and structural interventions, such as increased nurse to patient ratios and addressing equipment shortages, as these interventions make it easier for nurses to complete documentation [22].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Studies have shown various forms of education, including training on IV catheter handling, dressing, hand hygiene and hub disinfection could improve the compliance of health care workers on IV catheter management and effectively decrease IV CRI rates. [24,25] There have been an increasing number of hospital quality improvement efforts in Rwanda in the recent years offering specific examples of how these efforts have proved beneficial to the provision of basic care processes, [26] reducing waiting time, [27] documentation compliance, [28] and patient flow. [29] However, few published studies related specifically to reducing IV CRI in Rwanda exist.…”
Section: Introductionmentioning
confidence: 99%